Work instability perception in a sample of psychologists - Leibovich de Figueroa, Nora (2006)
Considering work instability as a contextual stressor we designed a specific instrument to assess how it is perceived by a group of psychologists: The Perceived Uneasiness in Work Instability - Psychologists Inventory (in Spanish, IMPIL-PS). The data were collected from a 44-subject sample, both male and female, residents of the City of Buenos Aires and Greater Buenos Aires. We present data referring to sample characteristics and the areas with the greatest impact of the stressor are indicated. Recent research on work instability as a contextual stressor point out its influence on subjects' performance and behaviour.
Keywords: Psychological assessment; Stressor; Work instability; Psychologists